The contribution of digital technologies to construction safety - Débora Pinto (2018)
Construction is still a sector with high incidence of accidents. Therefore, it's imperative to implement methodologies to improve safety in this sector. Building Information Modeling (BIM) emerges as a tool that allows the implementation of safety throughout the life cycle of a construction project, minimizing hazards and risks, consequently increasing safety. This paper aims to demonstrate BIM's methodology potential for the implementation of safety measures throughout planning and the application of this information on the worksite management. A case study based on BIM 4D was developed in which safety measures to prevent falls from height were applied. With 4D simulation, it is possible to follow the execution of work giving Safety Technicians the capability to visualize in each phase which measures should be implemented. In conclusion, BIM contributes to safety measures integration from the design phase to the construction phase, making safety management easier throughout all construction project phases.